SOCIOEMOTIONAL EDUCATION IN EARLY CHILDHOOD: PATHWAYS TO INTEGRAL AND AFFECTIVE DEVELOPMENT (International Seven Journal of Multidisciplinary, 2023)
Socioemotional education during early childhood is pivotal for fostering integral and affective development, laying foundations for emotional regulation, social competence, and lifelong well-being. This article synthesizes contemporary research demonstrating how socioemotional learning (SEL) programs enhance children's prosocial behavior, self-awareness, and cognitive skills. It highlights the neuroscientific underpinnings of early interventions and the critical role of caregivers and educators in nurturing emotional and social growth. Longitudinal evidence underscores the lasting impact of socioemotional education on reducing behavioral problems and improving academic success, supporting the case for its inclusion in early childhood curricula worldwide. The holistic development achieved through socioemotional education contributes not only to individual well-being but also to fostering resilient and cohesive communities.